2012
DOI: 10.1074/jbc.m112.350413
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Induced Pluripotent Stem Cells from Human Renal Proximal Tubular Cells with Only Two Transcription Factors, Oct4 and Sox2

Abstract: Background:The generation of human-induced pluripotent stem cells (iPS) has raised expectations for disease modeling, drug discovery, and cell therapy. Results: VP16-polycistronic vectors display enhanced reprogramming capacity. Conclusion: Primary tubular renal cells are amenable for iPSC reprogramming in the absence of oncogenes. Significance: Kidney-derived iPSCs provide a reliable cellular platform for the study of kidney pathology and drug discovery studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…We have cultured urine cells from patients with cryptorchidism and hypospadias, and these cells mainly expressed urothelial surface markers [10]. Genetically normal urine cells and kidney mesangial cells have been successfully reprogrammed during the preparation of this manuscript [29][30][31]. All these results, together with our urine-derived cryptorchid-specific iPS cell lines with genetic variations, demonstrate that urine cells are one of the most acceptable noninvasive sources of iPS cells, especially for research on pediatric diseases.…”
Section: Discussionmentioning
confidence: 88%
“…We have cultured urine cells from patients with cryptorchidism and hypospadias, and these cells mainly expressed urothelial surface markers [10]. Genetically normal urine cells and kidney mesangial cells have been successfully reprogrammed during the preparation of this manuscript [29][30][31]. All these results, together with our urine-derived cryptorchid-specific iPS cell lines with genetic variations, demonstrate that urine cells are one of the most acceptable noninvasive sources of iPS cells, especially for research on pediatric diseases.…”
Section: Discussionmentioning
confidence: 88%
“…This indicates that iPSC-like tumor cells generated in this study proceeded further in the reprogramming process than the F-class cells (Figure 2D). Similarly to early reports, we found that endogenous expression of reprogramming genes can compensate for ectopic expression (Utikal et al., 2009, Montserrat et al., 2012). This allowed us to reprogram the melanoma cells with OCT4, SOX2, and KLF4 only, without using the oncoprotein MYC.…”
Section: Discussionmentioning
confidence: 99%
“…79,80 It therefore is important that phenotypes be shown reproducibly in multiple patients, and if possible that rescue experiments be performed to show their specificity. 21 Experiments comparing hiPSCs reprogrammed from urine cells, kidney epithelial cells, or mesangial cells 68,81,82 also should take into account the possibility of injury or secondary mutations in the genitourinary systems of patients with disease, which could affect iPSC function. Recently developed genome editing tools, including transcription activator-like effector nucleases and the Cas9/clustered regularly interspersed short palindromic repeats system, can be applied to hPSCs to introduce or correct genetic mutations for analysis of cellular phenotypes on an isogenic genetic background, and may provide a useful complement to hiPSCs with naturally occurring genetic mutations.…”
Section: Patient-derived Hpsc Methodologies For the Study Of Kidney Dmentioning
confidence: 99%